RELEVANSI NILAI PENGUNGKAPAN INSTRUMEN KEUANGAN PERBANKAN INDONESIA: TELAAH PSAK 60 (REVISI 2014) - Nina Karina Karim; Elin Erlina Sasanti; Eni Indriani; Indria Puspitasari Lenap; Widyastuti Widyastuti (Jurnal Riset Akuntansi, 2018)
For go public banking entity, applying PSAK 60 (revised 2014) regarding disclosure of financial instruments in the financial statements is a necessity in order to provide information to readers of financial statements. Disclosure and presentation of information is a fundamental effort to provide information on financial statements for users of financial information. To be useful, accounting information must be relevant to meet the needs of users of financial statements in the decision making process. The purpose of this study is to examine the increased relevance of the value of disclosure of financial instruments after PSAK 60 (revised 2014) to banking company listed on the Indonesia Stock Exchange before and after PSAK 60 (revised 2014) is effective on 1 January 2015. The findings of this study indicated that somehow the quality of information disclosure of financial instrument has relevance to the decisions investors as reflected by the stock price. This is shown by the positive coefficient direction although the value of financial instrument disclosure coefficients shows the influence of financial instruments is not statistically significant, which indicates that the results of this study support the value relevance theory, whereby the higher level of financial instrument disclosure in the financial statements the higher the market value of equity firms.